Splenic cysts: Analysis of 16 cases - Hamed Golmohammadzadeh; Ghodratollah Maddah; Yavar shams hojjati; Abbas Abdollahi; Hossein Shabahang (Babol University of Medical Sciences, 2016)
Background: Splenic cysts are known as rare clinical encounter. Classifying into primary (true) and secondary cysts (pseudocysts), true cysts contain cellular epithelial lining and subdivided into parasitic and non-parasitic cysts. This study aimed to determine the outcome of treatment in patients with splenic cyst. Methods: All patients with splenic cyst who had been treated in Department of General Surgery of Ghaem and Omid teaching hospitals over a 24-year period were identified. The medical records of these 16 patients were reviewed. Results: The study patients included 11 females (68.75%) and 5 males (31.25%) with average age of 39.8 years. Fifteen cases had true cyst including 11 parasitic cysts (hydatid) and only one pseudocyst. 37.5% of the splenic cysts had coexistent cysts in liver, pelvis, omentum and paracolic regions. Nine patients underwent total splenectomy and 5 cases partial splenectomy and 2 remaining cases received conservative medical treatment. The size of the cysts varied from 6 to 25 centimeter with average size of 14.3 centimeter. All patients with hydatid cysts received albendazole postoperative medical treatment with albendazole for 6 months. All patients recovered after treatment. Conclusion: Open splenectomy whether total or partial is effective and safe in patients with splenec cysts with or without hydatidosis. The outcome of treatment is good without recurrences.